INTEGRATING ONLINE TEACHING ENGLISH AS A FOREIGN LANGUAGE - Ivanova, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Online education/e-learning has been increasingly adopted globally as it has served as the only tool accessible for teachers and students to maintain undisrupted learning during the coronavirus outbreak. The relevance of the article is determined by the need to define effective ways to implement online education in foreign language classes to produce a positive effect on the learning outcome. The purpose of the article is to present ways of providing English-as-a-foreign-language learners with an online course designed in the learning management system Moodle and aimed at enhancing students' foreign language skills. The work uses a logical method (theoretical), the study of the experience of educational organizations and personal pedagogical experience at Pskov Branch of the Academy of Federal Penal Service of Russia (empirical). The study described the diversity of Moodle structure particular tasks, its assessment procedure and present military students’ feedback about the impact of the course on their foreign language acquisition, developing learners' autonomy and soft skills. It explored what problems English-as-a-foreign-language learners had with their English language learning and what support they needed to gain the maximum benefits from the online learning environment. The outcome of the online education was a substantial increase in the learners' autonomy and an integrative development of foreign language skills and soft skills.